2012
DOI: 10.1177/145749691210100112
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Large Head Metal-on-Metal Hip Arthroplasties

Abstract: Background and Aims: total hip arthroplasty significantly improves patient's life quality. however, total joint replacement is associated with possible complications, such as dislocations, infections, fractures and periprosthetic osteolysis. the goal of this study was to evaluate a large head metal-on-metal total hip arthroplasties and analyse short term complications related to them.Material and Methods: between 9/2005 and 6/2009, a total of 691 hip replacements were performed on 635 patients with the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
1
10
1
3
Order By: Relevance
“…The total amount of Bimetric/ReCap combinations was high (5464). The short-term survival of Bimetric/ReCap with Magnum bearing surface has been promising also in previous studies (3,21,22). These data support the Australian finding of low short-term revision rate of ReCap THA.…”
Section: Discussionsupporting
confidence: 84%
“…The total amount of Bimetric/ReCap combinations was high (5464). The short-term survival of Bimetric/ReCap with Magnum bearing surface has been promising also in previous studies (3,21,22). These data support the Australian finding of low short-term revision rate of ReCap THA.…”
Section: Discussionsupporting
confidence: 84%
“…The Kaplan-Meier survival of 87% at 12 years in the current series of large-diameter MoM THAs with these components is somewhat lower than rates reported in combined data from Australia, England and Wales, and New Zealand [16], data from the Finnish Arthroplasty Register [47], and three independent series (Table 3) [29,44,60]. Component survival in the current study was lower than our earlier reported experience with 779 primary THAs with metal-on-improved polyethylene in which we observed 98% survival at 4 years [48].…”
Section: Discussioncontrasting
confidence: 65%
“…Amid numerous reports of high failure rates and concerning reports with ARMD, pseudotumors, and systemic complications to metal ions [1,6,9,16,19,20,24,31,35,40,46,47,53,54,56,63,65], three large-diameter MoM devices have been voluntarily recalled by the manufacturers: the Articular Surface Replacement (ASR) by DePuy (Warsaw, IN, USA), the Durom by Zimmer (Warsaw, IN, USA), and the R3 by Smith & Nephew (Memphis, TN, USA) [64]. Published studies have reported considerable variation in frequency of ARMD and failure for large-diameter devices [9,16,26,29,32,34,44,46,47,60]. Our center previously reported a higher frequency of revision in patients with MoM THA compared with metal-on-improved polyethylene THA [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reports of early clinical success of ReCap-M2a-Magnum THA (Kostensalo et al 2012, Meding et al 2012) and ReCap-Magnum hip resurfacing arthroplasty (HRA) (Gross and Liu 2012, van der Weegen et al 2012) were promising. The short-term survival of the ReCap-M2a-Magnum THA was comparable to that of conventional cemented THA based on data from the Finnish Arthroplasty Register (Mokka et al 2013).…”
Section: Discussionmentioning
confidence: 99%